If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3z + 5 = 26 Reorder the terms: 5 + -3z = 26 Solving 5 + -3z = 26 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3z = 26 + -5 Combine like terms: 5 + -5 = 0 0 + -3z = 26 + -5 -3z = 26 + -5 Combine like terms: 26 + -5 = 21 -3z = 21 Divide each side by '-3'. z = -7 Simplifying z = -7
| 3=-2y-1.6 | | 95-5x=65 | | 8=17-x | | y=4x+33 | | 156-22x=109-17x | | 27-x=27 | | 126+8m=254 | | x+x+2+x+4+x+6=344 | | f(3)=-3.3-2 | | -y=-9x+33 | | -8x-x=24x | | 3.64x+49=13.2496+7x | | -3=2p+1 | | 24n-98=238 | | (4xy^3)(3x^3y^5)= | | f(3)=-3(3)-2 | | Y-64=-3.50(x-0) | | 6.2x+31=62 | | ln(x+2)+ln(x-4)=ln(7) | | -6=3(w+6)-7w | | 8.7x+14=109.7 | | 6x+x^2=30 | | 6(-5r+8)= | | 33n-48=216 | | 16x+41=19x-103 | | -5+6=-34 | | 1=-1(-7)+x | | 3x=-2y-7 | | 9.36+k=18.8 | | 8y-3=15+29 | | -(x-7)-5=4(x+3)-6x | | -4.8+b+0.6b=1.8+3.6 |